2000
DOI: 10.1017/s0033291700001707
|View full text |Cite
|
Sign up to set email alerts
|

Depression and social stress in Pakistan

Abstract: This study confirms the high prevalence of depressive disorders in Pakistan and suggests that this may be higher than other developing countries because of the high proportion of the population who experience social adversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
126
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 20 publications
15
126
1
2
Order By: Relevance
“…However, in two international studies conducted in the rural area of Pakistan, high prevalence of CMD was identified among women of 66% and 57.5%, respectively (19)(20) . A different result was shown in a study in rural villages in India, where 22.8% of the 658 women participants were affected by CMD when the SRQ-20 was used (21) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in two international studies conducted in the rural area of Pakistan, high prevalence of CMD was identified among women of 66% and 57.5%, respectively (19)(20) . A different result was shown in a study in rural villages in India, where 22.8% of the 658 women participants were affected by CMD when the SRQ-20 was used (21) .…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, a study in the area of Zona da Mata in Pernambuco identified prevalence of CMD among the participating population (men and women) of 36.0%, and among women it was 44.17% (5) . In relation to the present study, a lower prevalence of CMD was evidenced in relation to the national studies in rural areas.However, in two international studies conducted in the rural area of Pakistan, high prevalence of CMD was identified among women of 66% and 57.5%, respectively (19)(20) . A different result was shown in a study in rural villages in India, where 22.8% of the 658 women participants were affected by CMD when the SRQ-20 was used (21) .…”
mentioning
confidence: 96%
“…49 Depression in these women has a complex etiology involving factors as diverse as poverty, marital conflict, domestic violence and lack of control over economic resources. 50 However, recent studies suggest that depression can be affordably treated in developing countries.…”
Section: Or and 95% CImentioning
confidence: 99%
“…A systematic review DEBT AND HEALTH suggested that wealth is related to health, and the authors suggest this should be used as an indicator of SES (Pollack, et al, 2007). Financial difficulties such as being unable to pay the bills also appear to be related to mental health (Butterworth, Rodgers, & Windsor, 2009;Husain, Creed, & Tomenson, 2000;Elina Laaksonen, et al, 2007;E. Laaksonen, et al, 2009), and physical health variables such as smoking (Kendzor, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%